Penerapan Sistem Pendukung Keputusan Dengan Metode Simple Multi Attribute Rating Technique Pada Pemilihan Toko Roti - Erene Gernaria Sihombing; Ester Arisawati; Linda Sari Dewi; Frisma Handayanna; Rinawati Rinawati (Universitas Islam Sumatera Utara, 2019)
Bakery is a place frequented by people as a place to buy bread to be given as a gift or food. The number of bakeries that are open in Pematangsiantar city makes consumers confused and need accurate information to decide to visit a bakery that suits their needs. Moreover, every bakery provides and offers their best products to consumers. The method used in decision making is the SMART method (Simple Multi Attribute Rating Technique) because SMART is a method in making multi-attribute decisions. This system can provide recommendations for bakeries that are in accordance with the expectations of consumers to be considered in choosing the right bakery, especially in pematangsiantar city where there are 5 bakeries namely: Double (A1), Aroma (A2), Francebakery (A3), Valetine ( A4) and My darling (A5). In this study there are 5 criteria that support the research objectives, namely: service (C1), texture (C2), taste (C3), price (C4) and location (C5). The research data was obtained by interviewing and giving questionnaires / questionnaires to 250 consumers. The results of the questionnaire were processed and calculated using the SMART method. Based on the results of the study, it is obtained double (A1) first rank with the final value of 0.8835, francebakery (A3) second rank with the final value of 0.5530 and my dear (A5) ranked third with the final value of 0.45. It is hoped that this research can provide input to consumers in recommending and choosing the best bakery in Pematangsiantar.